Dimmable electronic ballast with high power-factor SEPIC preregulator, for multiple tubular fluorescent lamps - Wakabayashi, Fabio Toshiaki [UNESP]; Canesin, Carlos Alberto [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2004)
An electronic ballast for multiple tubular fluorescent lamps is presented in this paper. The proposed structure features high power-factor, dimming capability, and soft-switching to the semiconductor devices operated in high frequencies. A Zero-Current-Switching - Pulse-Width-Modulated (ZCS-PWM) SEPIC converter composes the rectifying stage, controlled by the instantaneous average input current technique, performing soft-commutations and high input power factor. Regarding the inverting stage, it is composed by a classical resonant Half-Bridge converter, associated to Series Parallel-Loaded Resonant (SPLR) filters. The dimming control technique employed in this Half-Bridge inverter is based on the phase-shift in the current processed through the sets of filter + lamp. In addition, experimental results are shown in order to validate the developed analysis.
Keywords: Electronic ballasts; High power factor (HPF); Preregulators; Total harmonic distortion (THD); Diodes; Electric currents; Electric potential; Electric rectifiers; Ignition; Integrated circuits; Natural frequencies; Phase shift; Semiconductor devices; Switching; Fluorescent lamps